Towards a Methodology for a Corpus-Based Approach to Translation Evaluation - Bowker, Lynne (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2001)
AbstractTranslation evaluation is undoubtedly one of the most difficult tasks facing a translator trainer. It is unlikely that there will ever be a ready-made formula that will transform this task into a simple one; however, this article suggests that the task can be made somewhat easier by using a specially designed Evaluation Corpus that can act as a benchmark against which translator trainers can compare student translations.